ANALISIS TERHADAP ASAS FILSAFAT HUKUM ISLAM MENURUT BENI AHMAD SAEBANI - ., Nurmahmudah (Ahkam: Jurnal Hukum Islam, 2023)
This paper aims to find out the principles of Islamic law, namely the foundation, origin and principles of Islamic law in the perspective of philosophy in ontological, epistemological and axiological studies. The method used is library research, and analyzes the data analytically, critically, contemplatively, logically, systematically, structured, so as to understand the foundation or principle of Islamic law comprehensively. The result can be understood that al-Hakim is God who makes law has created rules with His iradah. The existence of an objective knowledge is one that does not depend on the existence or absence of the subject’s knowledge of the object of knowledge. So the knowledge of Allah, His Messenger, His books does not depend on human knowledge. So the Qur’an as a revelation in which there are laws of Allah’s creation is true by itself, so it has nothing to do with justification by humans. The laws made by Allah, making humans as subjects and objects, the law of truth is timeless, so that what changes is not His product, but the interpretation of it. Mukallaf or mahkum ’alaih (people affected by the burden of taklif), namely people who have baligh (adulthood) and reason can distinguish good and bad. In the process of extracting the law from the texts of the Qur’an and Hadith, we need the knowledge of Tafsir, Hadith Science, Fiqh Science, Ushul Fiqh. This effort is called ijtihad. So the principle of Islamic law is based on revelation which has strong arguments based on rational, empirical, and scientific evidence.